Manajemen Kepala Sekolah dalam Meningkatkan Kerja Sama dengan Dunia Industri - Ismiatun, Siti Rahma; Neliwati, Neliwati; Khairuddin, Khairuddin; Rofiq, Muhammad Husnur (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This research is specifically to find out how the principal's management is improving cooperation with the industrial world at SMK Muhammadiyah Rantau Prapat. This includes implementation planning, evaluation, and obstacles in improving cooperation with the industrial world. By knowing these things, some suggestions can be given that can be taken into consideration for school principals in increasing cooperation between the industrial world and schools. This research point uses a qualitative or naturalistic approach to describe the findings of the research. Data collection was done through participant observation techniques, interviews, and documentation while data analysis involved three stages, namely data reduction display data presentation, and verification of conclusions. The results of the study state that the principal's management at SMK Muhammadiyah Rantau Prapat has evaluation implementation planning and obstacles in establishing cooperation with the industrial world. Therefore, it can be understood that the main task of a school principal in carrying out his management is not only limited to the ability to implement programs, but more than that, the principal must be able to involve all levels of the organization, its members, and the community to take an active role so that they can make a positive contribution in achieving the objectives of the collaboration to be carried out. Planning for cooperation with the industrial world is illustrated by the involvement of the industrial world in carrying out school programs and the implementation of cooperation with the industrial world is carried out through an agreement with the industrial world to establish good cooperation. The evaluation carried out by the principal with the industrial world has the hope of improvement for the future in good cooperation and the obstacles found in establishing cooperation with the industrial world are limited resources and facilities in schools and other challenges faced by school principals are rapid changes in industry demands.